A disposição a pagar pela água como fundamento para investimento na proteção e recuperação de unidades de conservação: o caso do Parque Estadual da Pedra Branca, no Rio de Janeiro - Gonçalves, Celso da Silva (2008)
The objective of this is the monetary valuation of water as a basis for the valuation of the environmental services generated by a Conservation Units, based on a pilot study carried out in the buffer zone of the Pedra Branca State Park (PEPB), in Rio de Janeiro, Brazil. Applying the contingent valuation method, the research sought to identify the buffer zone population's Willingness to Pay (WTP) for this asset, essential to human life, obtained largely from water sources within the Park itself. To arrive at the WTP, a questionnaire was applied to a random sample of local households. The key question asked how much the families would be willing to pay in their monthly light bill to assure a regular supply of good quality water, through reforestation projects in the PEPB. The value found in this case was R$0.73 (about US$0.20 per family/month). This value was expended to all residents in the Park buffer zone, arriving at a total value of R$ 16,976.24 per year (about US$4,850). This amount, although modest, would be sufficient, for example, to keep five workers throughout the year reforesting areas currently covered by pastures within the Park. Allied with other initiatives of non-governmental organizations, governmental agencies and private companies already in progress in the PEPB, the residents could thus contribute in a significant way toward the preservation of the Park, and continue to benefit from water of good quality and adequate volume.